Basic Concept Of Steps In Reviewing Learning Materials To Create Quality Learning Materials - Yasin, Nur Ali; Fajri, Putri Nur (Literacy: Journal of Education and Social Science, 2025)
This article aims to discuss the basic concepts that need to be understood in conducting a review of teaching materials as a basis for developing quality learning practices. The method used is a literature review with a descriptive-qualitative approach to various theoretical sources and academic references. The results of the study indicate that understanding the meaning, function, types of teaching materials, and principles and steps in reviewing teaching materials is very important for teachers in designing effective learning. By understanding these concepts, teachers can conduct a review of teaching materials more systematically and in accordance with curriculum demands, student characteristics, and learning objectives. This study provides a conceptual basis for the development of relevant, contextual, and quality learning tools.